Effects of OsMSH6 Mutations on Microsatellite Stability and Homeologous Recombination in Rice - Jiang, Meng; Wu, Xiaojiang; Song, Yue; Shen, Hongzhe; Cui, Hairui (Frontiers in Plant Science, 2020)
DNA mismatch repair (MMR) system is important for maintaining DNA replication fidelity and genome stability by repairing erroneous deletions, insertions and mis-incorporation of bases. With the aim of deciphering the role of the MMR system in genome stability and recombination in rice, we investigated the function of OsMSH6 gene, an import component of the MMR system. To achieve this goal, homeologous recombination and endogenous microsatellite stability were evaluated by using rice mutants carrying a Tos17 insertion into the OsMSH6 gene. Totally 60 microsatellites were analyzed and 15 distributed on chromosome 3, 6, 8 and 10 showed instability in three OsMSH6 mutants, D6011, NF7784 and NF9010, compared with the wild type MSH6WT (the control). The disruption of OsMSH6 gene is associated with modest increases in homeologous recombination, ranging from 2.0% to 32.5% on chromosome 1, 3, 9 and 10 in the BCF2 populations of the mutant ND6011 and NF9010. Our results suggest that the OsMSH6 plays an important role in ensuring genome stability and genetic recombination, providing the first evidence for the MSH6 gene in maintaining microsatellite stability and restricting homeologous recombination in plants.